Smart "Health of Things": a Model Based in Data Mining for an IoT Health System Used in Hospital and Home Urgencies - Braga, Oton C.; Mendes Neto, Francisco M.; Oliveira, Antônio M. B. de; Costa Filho, Raimundo Valter (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2019)
Studies indicate that the life expectancy of Brazilians is increasing, leading to an aging population and growing the number of people in home care. In this paper, a model is developed that generates alerts that may prevent urgent situations to patients and caregivers in the hospital and homecare environment. These alerts are generated from vital signs captured by wearable devices combined with standards from an unsupervised machine learning model that identifies risk situations. This work is the intelligent module of the "Health of Things", a project composed of hardware components (smartwatch prototype with measurement sensors), mobile application, web system, digital TV and FHIR API.